Digital Political Rhetoric of Moderate Islamic Mass-Based Parties in Southeast Asia: A Critical Discourse Analysis of PAN (Indonesia) and AMANAH (Malaysia) - Iding Rosyidin; Nikita Kuklin (Jurnal Ilmu Sosial Indonesia (JISI), 2026)
The development of digital technology has transformed political communication practices among moderate Islamic political parties in Southeast Asia. The National Mandate Party (PAN) in Indonesia and the State Trust Party  (AMANAH) in Malaysia utilize digital media to construct political images, expand support bases, and promote narratives of Islamic moderation amid the rise of identity politics and religious populism. This study analyzes the digital political rhetoric of PAN and AMANAH using Teun A. van Dijk’s Critical Discourse Analysis (CDA). Employing a qualitative method with case study approach, the research examines social media posts between 2022 and 2025. The analysis focuses on three dimensions: textual structure, social cognition, and social context. The findings indicate that both parties promote moderate Islamic values through discourses of inclusivity, democracy, nationalism, and tolerance. However, their rhetorical orientations differ. PAN combines Islamic symbolism with national political pragmatism, while AMANAH emphasizes progressive Islamic reformism and multicultural values within the Malaysian context. In the digital sphere, both parties use social media to disseminate ideological narratives, shape leadership images, and negotiate contemporary Islamic identities. The study concludes that digital political rhetoric functions not only as a communication strategy but also as an ideological instrument through which moderate Islamic parties maintain political legitimacy in the increasingly competitive digital political landscape of Southeast Asia.